Relying on ST Segment Depression alone to Predict Ischemic Heart Disease- How Far We can Go ? - Alam, Md Mashiul; Rahman, Md Mukhlesur; Parvin, Tanjima; Ahmed, Khurshed; Habib, SM Ahsan; Khaled, Md Fakhrul Islam; Islam, Md Azharul; Shahin, Md Ahasanul Kabir; Siddiki, Kamruzzaman; Amin, Md Al (University Heart Journal, 2020)
Introduction: Ischemic heart disease (IHD) or coronary artery disease (CAD) has become predominant cause of death across the world and frequently stable angina, which is the most common presentation of this disease, gives hard time to reach a proper diagnosis due to duality of non-invasive testing. While Exercise Treadmill Test (ETT) is an inexpensive non-invasive modality which may have many output depending on method of interpretation, ST segment depression is much utilized but traditionally less perfect than available treadmill scores. We have compared its accuracy to Duke Treadmill Score (DTS), Simple Treadmill Score (STS) and Cleveland Clinic Score (CCS) among Bangladesh people to generate a local insight. Objective: To estimate and compare accuracy of ST segment response, DTS, Simple Treadmill Score and Cleveland Clinic Score to predict CAD. Method: In a cross-sectional study total 130 patients who had visited at a medical university with stable chest pain were selected according to predefined inclusion and exclusion criteria over one year. After taking proper history and physical examination their ETT report and Coronary Angiogram (CAG) finding, which were done according to indication defined by their consultants. ETT interpretation as ST segment response and treadmill scores were compared with gold standard test for CAD that is CAG. Accuracy of STdepression and treadmill scores were calculated by the formula “Accuracy = TP+TN / Total Sample”. Result: Among the total sample (n=130) male and female were 93 & 37, respectively. Nearly half of male sample fell into 5th decade and around same portion of female sample was in 4th decade. About 58%, 28% & 14% patients came with typical, atypical & non-cardiac chest pain. As calculated with above mentioned formula accuracy of ST segment response alone to diagnose IHD came about 68.4% (p value 0.004). Similarly DTS, STS and CCS had 83.3%, 83.9% and 77.2% accuracy, respectively (p value 0.000). Conclusion: During ETT relying on ST segment depression alone to diagnose CAD is significantly less accurate than treadmill scores namely, Duke Treadmill Score, Simple treadmill Score or Cleveland Clinic Score. Applying any of these treadmill scores during exercise test interpretation can identify ischemic heart disease patients with more accuracy. University Heart Journal Vol. 17, No. 1, Jan 2021; 10-15